The association between dietary flavonoid and lignan intakes and incident type 2 diabetes in European populations: the EPIC-InterAct study. - Zamora-Ros, R; Forouhi, N; Sharp, S; González, C; Buijsse, B; Guevara, M; van der Schouw, Y; Amiano, P; Boeing, H; Bredsdorff, L; Clavel-Chapelon, F; Fagherazzi, G; et al. (2013)
OBJECTIVE: To study the association between dietary flavonoid and lignan intakes, and the risk of development of type 2 diabetes among European populations. RESEARCH DESIGN AND METHODS: The European Prospective Investigation into Cancer and Nutrition-InterAct case-cohort study included 12,403 incident type 2 diabetes cases and a stratified subcohort of 16,154 participants from among 340,234 participants with 3.99 million person-years of follow-up in eight European countries. At baseline, country-specific validated dietary questionnaires were used. A flavonoid and lignan food composition database was developed from the Phenol-Explorer, the U.K. Food Standards Agency, and the U.S. Department of Agriculture databases. Hazard ratios (HRs) from country-specific Prentice-weighted Cox regression models were pooled using random-effects meta-analysis. RESULTS: In multivariable models, a trend for an inverse association between total flavonoid intake and type 2 diabetes was observed (HR for the highest vs. the lowest quintile, 0.90 [95% CI 0.77-1.04]; P value trend = 0.040), but not with lignans (HR 0.88 [95% CI 0.72-1.07]; P value trend = 0.119). Among flavonoid subclasses, flavonols (HR 0.81 [95% CI 0.69-0.95]; P value trend = 0.020) and flavanols (HR 0.82 [95% CI 0.68-0.99]; P value trend = 0.012), including flavan-3-ol monomers (HR 0.73 [95% CI 0.57-0.93]; P value trend = 0.029), were associated with a significantly reduced hazard of diabetes. CONCLUSIONS: Prospective findings in this large European cohort demonstrate inverse associations between flavonoids, particularly flavanols and flavonols, and incident type 2 diabetes. This suggests a potential protective role of eating a diet rich in flavonoids, a dietary pattern based on plant-based foods, in the prevention of type 2 diabetes.